The Relationship Between Social Presence and Language Anxiety for English as a Foreign Language Learners: A Community of Inquiry Perspective - د. بسمة بنت علي أبوغرارة (مجلة العلوم التربوية والنفسية, 2025)
This study explored the relationship between social presence and language anxiety in online language learning environments. It involved a diverse group of 220 first-year English as a foreign language learner enrolled in an English language course at Taibah University in Saudi Arabia. Quantitative analysis revealed a statistically significant negative correlation between key dimensions of social presence—affective expression, open communication and group cohesion—and language anxiety. Complementary qualitative findings highlighted themes such as a supportive learning environment, peer interaction and the role of familiarity in reducing anxiety. These results indicate the importance of fostering a strong sense of connection between learners, peers and an instructor to reduce language anxiety. Key recommendations include adopting a multifaceted approach to enhancing social presence, supportive environments, peer interactions and addressing technological barriers. Future research should investigate the long-term effects of these strategies and account for learners’ differences to develop best practices for instructors. Keywords: social presence, language anxiety, online learning, EFL learning